The new paradigm of solution dolines - Resnik Planinc, Tatjana (Geografski vestnik, 2016)
The paper focuses on the morphogenesis of solution dolines from a theoretical aspect. First of all, the classical paradigm of solution dolines is evaluated, followed by a review of contemporary understandings of karst processes. The author seeks to examine the shift from old concepts within karstology to new concepts and paradigms, although obsolete ideas are still present in lecture books and curricula/syllabi. The problem of altering paradigms is presented using the example of solution dolines, the most typical karst landform, and discussed further through the prism of changing deeply rooted paradigms in the educational process
Keywords: curriculum; karst; korozija; kras (geologija); krasoslovje; kraški pojavi; kurikulum; učbeniki; vrtače